Pengaruh Model Pembelajaran Problem Based Learning (PBL) Menggunakan Media Power Point Terhadap Hasil Belajar Fisika Siswa - Nurul Asriah; Badrul Wajdi; Khaerus Syahidi; Ria Hastiarna (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
This research purposed at knowing the effect of Problem Based Learning (PBL) utilizing Power Point media on the students’ physics learning achievement at VIII grade of MTs Muallimat NW Pancor. This research was experiment. The population of this research was students at VIII class of MTs Muallimat NW Pancor. The sample was VIII-E as the experiment class and VIII-C as the control class. The research design used was post-test only control group design. The data collection techniques used was test in from multiple choice. The data analysis technique used for testing the hypothesis was one-way t-test. The result of the hypothesis showed that tcount > ttable (1.78 > 1.675), it means that Ho was rejected and Ha was accepted, so it can be concluded that there was effect of Problem Based Learning (PBL) utilizing Power Point media on the students’ physics learning achievement at VIII grade of MTs Muallimat NW Pancor.